Web-Based Inventory Information System Using First-In First-Out (FIFO) Algorithm at CV Dewangga - Mandalangi, Raudatul Jenah; Sara, Kristina; Mando, L B Finansius (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The development of information technology has encouraged companies to adapt in order to improve operational effectiveness and efficiency, particularly in inventory management. CV Dewangga, a company engaged in the distribution of office supplies, still relies on a manual system using book records and simple documents. This condition often leads to problems such as delays in stock checking, inaccurate data entry, difficulties in tracking incoming and outgoing goods, and late report preparation. This study aims to design and develop a web-based inventory information system by implementing the First-In First-Out (FIFO) algorithm to ensure that items entering earlier are also issued first, thereby minimizing the risk of old stock accumulation. The research method applied is Rapid Application Development (RAD), whichconsists of requirement analysis, design, implementation, and testing. Research data were collected through direct observation at CV Dewangga and interviews with staff regarding the inventory workflow. The developed system provides features for real-time recording of incoming and outgoing goods, FIFO-based stock management, and automated report generation. Testing using the black-box method confirmed that all system functions operate as required. The findings indicate significant improvements in data accuracy, reporting speed, and inventory efficiency compared to manual methods. This study contributes by presenting a practical web-based inventory system model suitable for small and medium enterprises (SMEs). The implication is to encourage the digitalization of inventory management to enhance competitiveness in the Industry 4.0 era.